Change in body composition of female junior volleyball players - Pavlik, J.; Vespalec, T.; Zeman, T. (Journal of Human Sport & Exercise, 2016)
The purpose of our study is to monitor and analyze the composition of selected body masses of female v junior volleyball players. The data were obtained from 18 players, aged 14 to 19 years, of the Královo Pole volleyball club in Brno, Czech Republic (VV KP Brno), between 1 August 2014 and 20 December 2014. Body composition was measured by Inbody 230 - Biospace using the bioimpedance measurement method. We obtained the following data from measurement: BMI (Body Mass Index), PBF (Percentage Body Fat), body mass, muscle and fat mass of both upper and lower limbs and the trunk. Mann-Whitney U test is used to compare differences between the values obtained before the preseason preparation, after the preseason preparation and after three months of the season. All statistical computations were performed using R software (R Core Team 2013). Comparing the results after the preliminary part we diagnosed a significant difference (p<0.05) increase of percentage of total fat mass (p=0.0266). After the preliminary part of the season significant difference describing increase of body mass (p=0.0462) was found, together with increase of body fat in left upper (p=0.0313), right upper (p=0.0429) limb and with increase of trunk mass (p=0.0379). The study revealed interesting information about a change of the body mass and body fat percentage of volleyball players of VK KP Brno during the regular season. The findings from the preseason preparation confirmed the expected change, i.e. that the muscle mass increases while the body mass and body fat percentage decrease.